Marketing Efficiency Analysis of Robusta Coffee Commodity in Dampit District, Malang Regency - Titania Audi Pristiani; Fatchur Rozci; Pawana Nur Indah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Dampit District, Malang Regency, is known as the largest producer of robusta coffee, with a production of 5,464 tons in 2022. Dampit's robusta coffee is globally recognized for its quality, with nearly 90% of the production exported. Farmers in this region have added value to their coffee by processing it from coffee cherries into green beans (coffee ose), which increases their income. However, tight market competition and limited farmer knowledge about marketing margins pose challenges. This study aims to analyze the product flow and marketing efficiency of Dampit's robusta coffee through marketing margin and farmers' share analyses. The research employed a qualitative descriptive method, using interviews to map the product flow into a supply chain scheme. Marketing margin and farmers' share analyses were used to evaluate efficiency. The findings identified three product flow patterns involving farmers, collectors, small traders, and large traders. Pattern II proved to be the most efficient, with a total margin of IDR 20,000 and the highest farmer's share at 76.4%. This pattern allows farmers to receive the largest share of income compared to other patterns. These results offer recommendations to enhance the welfare of robusta coffee farmers in Dampit District by optimizing efficient marketing patterns.